Analisis Spasio-Temporal Tutupan Lahan dan LST AST di Universitas Indonesia dan Kawasan Perpustakaan Universitas Indonesia - Fahmy Iqbal; Auliany, Fajriya Kurnia; Permata, Cheryl Ferrarichka; Gabriel, Gabriel; Al Asy Ari, Abi Musa (Jurnal Sains Geografi, 2025)
This study analyzed the spatio-temporal dynamics of Land Surface Temperature (LST) and Air Surface Temperature (AST) in Universitas Indonesia and the surrounding areas of the Faculty of Computer Science and University Library. Satellite imagery from Landsat 8 OLI/TIRS acquired in 2014, 2015, and 2025 was processed to estimate LST values, which were then converted into AST using linear regression models. Data processing and analysis were conducted using Google Earth Engine and ArcGIS Pro. The results showed a consistent increase in both LST and AST over time. LST experienced an increase of 15.82%, rising from 35.4°C in the 2014–2015 period to 41°C in May 2025, with an extreme maximum temperature reaching 50°C. Spatially, areas with dense vegetation and water bodies exhibited lower temperatures, whereas built-up areas displayed higher temperature values. Isotherm maps and kriging interpolation revealed temperature distributions closely related to land cover characteristics. These findings indicate that changes in land cover significantly influence the thermal conditions of the campus environment and provide valuable input for sustainable spatial planning.